Differences in the rates of seroma complications between hernial sac transection and reduction after laparoscopic inguinal hernia repair: systematic review and meta-analysis - Chairat Supsamutchai; Ratanakiat Pongratanakul; Jakrapan Jirasiritham; Puvee Punmeechao; Napaphat Poprom; Jarinya Wilasrusmee; Theejutha Meakleartmongkol; Settanan Plangsiri; Chumpon Wilasrusmee (Scientific Reports)
Abstract Seroma formation is one of the most common postoperative complications after laparoscopic inguinal hernia repair (LIHR). Many techniques to reduce the incidence of seroma formation after LIHR have been described; however, the evidence for performing hernial sac transection (HST) technique is limited. Therefore, this study was conceived to evaluate the effect of HST on LIHR. We conducted a systematic review and meta-analysis of comparative studies according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) 2020. The PubMed, Embase, Springer, and the Cochrane databases were searched for relevant publications up to December 2023. Studies concerning laparoscopic inguinal hernia repair with clearly specified surgical techniques were included. Studies were excluded if they were open procedures or non-inguinal hernia repair. Egger’s test and funnel plot analysis was used to assess bias. Outcomes were reported as odds ratio for dichotomous outcomes and as confidence intervals for continuous outcomes. No funding was received for this study. The study protocol was registered in PROSPERO under the number ID: CRD.42,024,530,115. A total of 3,076 patients in 9 studies were included in the analysis (4 RCTs, 4 retrospective cohorts, and 1 prospective cohort). Three, four, and two studies evaluated TEP, TAAP, and both techniques, respectively. The rate of seroma in HST transection was 57% lower than that in the reduction method (p value < 0.01), with low evidence of publication bias (Egger test and funnel plots, coefficient, 0.470; SE, 0.722; p = 0.275). In the subgroup analysis, 3 RCTs reported lower rates of seroma formation in HST (RR, 0.57; 95% CI, -0.24, 1.37), but the difference was not statistically significant. The rate of seroma formation in the HST for the TAPP method was significantly lower than that for the reduction method by approximately 53% (p value = 0.03). Compared with complete sac reduction, HST is associated with a lower seroma rate after LIHR.